The Development of Learning Media Based on Malangan Ethnomathematics to Support Self-Regulated Learning of Junior High School Students: Pengembangan Media Pembelajaran Berbasis Etnomatematika Budaya Malangan Guna Mendukung Self-Regulated Learning Siswa SMP - M. Nashihul Mukminin M. Nashihul Mukminin (Euclid, 2025)
Abstract Self-regulated learning (SLR) is one of the important things in students' education and self-development. However, based on previous researchers, students' SLR abilities are still quite low. Thus, the purpose of this research is to develop mathematics learning media based on Malangan cultural ethnomathematics to support SLR for junior high school students. The research procedure uses the ADDIE development model. The results of the study obtained Etno-Pro media on valid ratio and proportion material with an average media validity of 3.15 and an average material validity of 3.18. The practicality test results through teacher and student response questionnaires obtained an average of 3.7 with high practicality criteria. As many as 90.9% of students got a complete score with an average student test score of 87.4. The results also that there was an increase in students' SLR skills. This shows that Etno-Pro media can support students' SLR.